Proposta de parametrização de objetos BIM em atendimento à norma de manutenção de edificações NBR 5674:2012 - Nínive Cardoso Resende Lara (2021)
This research presents some procedures intended to help the maintenance management of a multifamily residential building by means of new processes referred in Building Information Modelling (BIM). For that purpose, the study uses the Revit, COBie and ARCHIBUS tools. The main goal of this work is to check how to process data parameterization in order to meet specific requirements of standard NBR 5674:2012. According to the Design Science Research (DSR) method, information for the elaboration of a maintenance schedule has been structured into a guidance framework. The facility example adopted for simulating the addition of non-geometrical information was the air conditioning system of a multifamily residential building. The present study checked how COBie data are used for maintenance management with BIM-FM tools, as well as the procedures for managing a building maintenance using the ARCHIBUS software. The main contribution of this research is the proposal of a BIM-FM guidance framework consisting in a structure of requirements for geometrical and non-geometrical information, which is to be added to BIM models in order to meet the maintenance schedule for all systems in a multifamily residential building. The performed procedures make it easier to organize the information that will be added to the BIM model, as well as to meet the NBR 5674:2012 requirement of stablishing a maintenance schedule, not to mention helping to better visualize information about the equipment to be repaired with easy data tracking.